Cerebrospinal fluid proteomics in children during induction for acute lymphoblastic leukemia: A pilot study. Issue 7 (23rd March 2015) - Priola, Ginna M.; Foster, Matthew W.; Deal, Allison M.; Richardson, Brenna M.; Thompson, J. Will; Blatt, Julie
Abstract Background Thrombosis in patients with acute lymphocytic leukemia (ALL) can develop after treatment with L‐asparaginase (asp) and is often localized to the central nervous system (CNS). We hypothesize that changes in the cerebrospinal fluid (CSF) proteome will occur after asp therapy and will anticipate CNS clots. Methods Five newly diagnosed patients, ages 1–11 years, with ALL (n = 4) or lymphoblastic lymphoma (LL) (n = 1) underwent serial lumbar punctures during induction. CSF was depleted of abundant plasma proteins and analyzed by gel‐free, label‐free quantitative proteomics. Results More than 600 proteins were quantified across all CSF samples. In four subjects, the expression of proteins involved in coagulation such as protein C Inhibitor (SERPINA5) and heparin cofactor II (SERPIND1) changed over the course of asp therapy. Antithrombin III (ATIII) and plasminogen (PLMN) levels were shown to have decreased expression over time in one child who developed a CNS thrombosis, compared to other subjects. Conclusions CSF proteomics is feasible and reproducible in ALL and LL. CSF ATIII and PLMN should be further investigated as predictive markers of CNS thrombosis. Pediatr Blood Cancer 2015;62:1190–1194. © 2015 Wiley Periodicals, Inc.